2009
DOI: 10.1007/s00384-009-0671-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic or open surgery for the cancer of the middle and lower rectum short-term outcomes of a comparative non-randomised study

Abstract: Less morbidity and faster recovery is offered after laparoscopic TME. Quality of surgery assessed by histopathology is similar between the approaches. Neoadjuvant chemoradiation seems to have significant impact on blood loss but results in longer operation times of the OPEN group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…Many nonrandomized [1][2][3][4] and randomized [5][6][7] studies have shown it to be associated with less blood loss, earlier recovery of bowel function, and shorter hospital stay without compromised oncologic outcomes. Metaanalyses comparing the two approaches for patients with rectal cancer have shown less postoperative morbidity [8] and earlier postoperative recovery [9, 10] after laparoscopic surgery, with comparable oncologic adequacy between the two [9, 11].…”
mentioning
confidence: 97%
“…Many nonrandomized [1][2][3][4] and randomized [5][6][7] studies have shown it to be associated with less blood loss, earlier recovery of bowel function, and shorter hospital stay without compromised oncologic outcomes. Metaanalyses comparing the two approaches for patients with rectal cancer have shown less postoperative morbidity [8] and earlier postoperative recovery [9, 10] after laparoscopic surgery, with comparable oncologic adequacy between the two [9, 11].…”
mentioning
confidence: 97%
“…Several studies compared long-term outcomes of patients with low rectal cancer between laparoscopic and open procedures. Almost all these studies demonstrated that long-term oncologic outcome of laparoscopic approach is comparable with open APR (10)(11)(12)(13)(14)(15)(16)(20)(21)(22). The problem for addressing this issue is relative rarity of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the laparoscopic APR requires appropriate equipment and a skilled surgeon. Shortand long-term outcomes of laparoscopic APR have been evaluated extensively (9)(10)(11)(12)(13)(14)(15). It has been demonstrated that laparoscopic APR is associated with better and faster bowel function recovery, less blood loss, shorter hospitalization and better rectal cancer prognosis and outcome (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases with a very low rectal carcinoma and favorable T-stage (I or II), an intersphincteric resection of the rectum and a handsewn coloanal anastomosis were offered. The laparoscopic approach has been previously described in detail [13,14,16]. Conversion of a laparoscopic procedure to open was defined as inability to complete the operation laparoscopically and an abdominal incision other than the initially planned was performed to complete the procedure.…”
Section: Surgical Interventionsmentioning
confidence: 99%